Process evaluation for the Care Homes Independent Pharmacist Prescriber Study (CHIPPS) - Linda Birt; Lindsay Dalgarno; David J Wright; Mohammed Alharthi; Jackie Inch; Maureen Spargo; Jeanette Blacklock; Fiona Poland; Richard C Holland; David P. Alldred; Carmel M. Hughes; Christine M. Bond; et al. (BMC, 2021)
Abstract Background Medicines management in care homes requires significant improvement. CHIPPS was a cluster randomised controlled trial to determine the effectiveness of integrating pharmacist independent prescribers into care homes to assume central responsibility for medicines management. This paper reports the parallel mixed-methods process evaluation. Method Intervention arm consisted of 25 triads: Care homes (staff and up to 24 residents), General Practitioner (GP) and Pharmacist Independent Prescriber (PIP). Data sources were pharmaceutical care plans (PCPs), pharmacist activity logs, online questionnaires and semi-structured interviews. Quantitative data were analysed descriptively. Qualitative data were analysed thematically. Results were mapped to the process evaluation objectives following the Medical Research Council framework. Results PCPs and activity logs were available from 22 PIPs. Questionnaires were returned by 16 PIPs, eight GPs, and two care home managers. Interviews were completed with 14 PIPs, eight GPs, nine care home managers, six care home staff, and one resident. All stakeholders reported some benefits from PIPs having responsibility for medicine management and identified no safety concerns. PIPs reported an increase in their knowledge and identified the value of having time to engage with care home staff and residents during reviews. The research paperwork was identified as least useful by many PIPs. PIPs conducted medication reviews on residents, recording 566 clinical interventions, many involving deprescribing; 93.8% of changes were sustained at 6 months. For 284 (50.2%) residents a medicine was stopped, and for a quarter of residents, changes involved a medicine linked to increased falls risk. Qualitative data indicated participants noted increased medication safety and improved resident quality of life. Contextual barriers to implementation were apparent in the few triads where PIP was not known previously to the GP and care home before the trial. In three triads, PIPs did not deliver the intervention. Conclusions The intervention was generally implemented as intended, and well-received by most stakeholders. Whilst there was widespread deprescribing, contextual factors effected opportunity for PIP engagement in care homes. Implementation was most effective when communication pathways between PIP and GP had been previously well-established. Trial registration The definitive RCT was registered with the ISRCTN registry (registration number  ISRCTN 17847169 ).